Kidney tea [Orthosiphon aristatus (Blume) Miq.] improves diabetic nephropathy via regulating gut microbiota and ferroptosis - Zhou, Zheng; Niu, Hongjuan; Bian, Meng; Zhu, Chunsheng (Frontiers in Pharmacology, 2024)
Introduction: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease. Due to its complex pathogenesis, new therapeutic agents are urgently needed. Orthosiphon aristatus (Blume) Miq., commonly known as kidney tea, is widely used in DN treatment in China. However, the mechanisms have not been fully elucidated. Methods: We used db/db mice as the DN model and evaluated the efficacy of kidney tea in DN treatment by measuring fasting blood glucose (FBG), serum inflammatory cytokines, renal injury indicators and histopathological changes. Furthermore, 16S rDNA gene sequencing, untargeted serum metabolomics, electron microscope, ELISA, qRT-PCR, and western blotting were performed to explore the mechanisms by which kidney tea exerted therapeutic effects. Results: Twelve polyphenols were identified from kidney tea, and its extract ameliorated FBG, inflammation and renal injury in DN mice. Moreover, kidney tea reshaped the gut microbiota, reduced the abundance of Muribaculaceae, Lachnoclostridium, Prevotellaceae_UCG-001, Corynebacterium and Akkermansia, and enriched the abundance of Alloprevotella, Blautia and Lachnospiraceae_NK4A136_group. Kidney tea altered the levels of serum metabolites in pathways such as ferroptosis, arginine biosynthesis and mTOR signaling pathway. Importantly, kidney tea improved mitochondrial damage, increased SOD activity, and decreased the levels of MDA and 4-HNE in the renal tissues of DN mice. Meanwhile, this functional tea up-regulated GPX4 and FTH1 expression and down-regulated ACSL4 and NCOA4 expression, indicating that it could inhibit ferroptosis in the kidneys. Conclusion: Our findings imply that kidney tea can attenuate DN development by modulating gut microbiota and ferroptosis, which presents a novel scientific rationale for the clinical application of kidney tea.